2013
DOI: 10.1002/acp.2949
|View full text |Cite
|
Sign up to set email alerts
|

Unhindered Spatial Processing During Route Memorization is Required to Maximize Both Spatial and Verbal Route Knowledge

Abstract: To successfully remember a route in a physical environment, individuals are believed to process and store both verbal and spatial information of that route. The present study tested whether both spatial and verbal contents are necessary to form an effective route memory. For that purpose, route learning was performed in three concurrent task conditions (spatial, verbal and control) and appraised at two moments in time, via three route memory tests (spatial, verbal and spatial-verbal). Results showed that route… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Visuospatial and central executive working memory were found to be more involved in using, than developing, mental representations of an environment (Brunyé & Taylor, 2008 ). Visual and spatial working memory (especially the latter) were involved in encoding of route and survey knowledge (Labate et al, 2014 ; Van Doorn & Blokland, 2014 ), and switching perspectives (route or survey) between learning and testing (Meneghetti, Labate, Pazzaglia, Hamilton, & Gyselinck, 2016 ). Several studies have examined how differences in SOD are related to differences in the use of working memory.…”
Section: Discussionmentioning
confidence: 99%
“…Visuospatial and central executive working memory were found to be more involved in using, than developing, mental representations of an environment (Brunyé & Taylor, 2008 ). Visual and spatial working memory (especially the latter) were involved in encoding of route and survey knowledge (Labate et al, 2014 ; Van Doorn & Blokland, 2014 ), and switching perspectives (route or survey) between learning and testing (Meneghetti, Labate, Pazzaglia, Hamilton, & Gyselinck, 2016 ). Several studies have examined how differences in SOD are related to differences in the use of working memory.…”
Section: Discussionmentioning
confidence: 99%
“… Purser et al (2012) have also reported a correlation between route learning and digit span for children 5–11 years of age. It is reasonable to presume that some aspects of route learning involve verbal memory to facilitate coding and maintaining the sequence of landmarks and turns that are encountered ( Van Doorn and Blokland, 2014 ). In fact, having landmarks available and having landmarks verbally labeled benefits route learning of children and adults ( Jansen-Osmann and Wiedenbauer, 2004a ; Lingwood et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intervention Mapping is analogous to route mapping in which a route planner determines where she is now and plans the way to find a destination (van Doorn & Blokland, 2014). Similar to a mapped route, IM planners create visual information aids such as tables and diagrams that function as landmarks on their route.…”
Section: Discussionmentioning
confidence: 99%